Metformin in Type 2 Diabetes: Evidence for its Beneficial Effects on Frailty and Sarcopenia - Pyrgioti, Elisavet E.; Karakousis, Nikolaos D.; Georgakopoulos, Petros N.; Papanas, Nikolaos (Current Diabetes Reviews, 2024)
This narrative review aimed to discuss the potential interplay among frailty syndrome, sarcopenia and metformin in type 2 diabetes mellitus (T2DM). There is emerging evidence on the potential protective role of metformin on both frailty and sarcopenia. However, results are not always consistent. Thus, further research is needed to provide a definitive answer on any role of metformin in improving frailty and/or sarcopenia in T2DM.
Keywords: frailty